THE COMPARISON OF HEALTH CONSCIOUSNESS INFLUENCE TOWARD PURCHASE INTENTION TO COW MILK AND SOY MILK - Putra, Aditya Perdana; Harianto, Harianto; Harmini, Harmini (Agric, 2024)
Nowadays consumers tend to substitute their habits in consuming cow milk into soy milk since it has reliability on health issue, taste, and healthy lifestyle. Referencing to prior researches, health consciousness and main theory of planned behavior (TPB) factors including attitude, subjective norms, and perceived behavioral control significantly influence consumer purchase intention. Researchers aimed to analyze health consciousness influence toward consumer purchase intention to cow milk and soy milk and formulate managerial implications to escalate consumer purchase intention to cow milk and soy milk. This research was conducted in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) area from October 2023 until April 2024 with 300 respondents. Researchers used voluntary response sampling as sampling method. Analysis methods used by researchers were descriptive analysis, structural equation modelling-partial least square (SEM-PLS) analysis, and importance performance matrix (IPMA) analysis. Results showed that health consciousness doesn’t influence purchase intention to cow milk significantly yet influences purchase intention to soy milk significantly. Otherwise trust, attitude, subjective norms, and perceived behavioral control influence purchase intention to both milks significantly. Furthermore, consumer purchase intention toward cow milk and soy milk can be escalated through improving performances of trust and subjective norms. For trust, producer needs to promote producer reputation, keep up the production standards, and design informative and attractive packaging. For subjective norms, producer needs to conceptualize informative and attractive advertising, conducting sales promotion, public relation, personal selling, and direct marketing.